2021
DOI: 10.3389/fcell.2021.684643
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Individualized Ubiquitin Prognostic Signature for Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is a common tumor type in genitourinary system and has a poor prognosis. Ubiquitin dependent modification systems have been reported in a variety of malignancies and have influenced tumor genesis and progression. However, the molecular characteristics and prognostic value of ubiquitin in ccRCC have not been systematically reported. In our study, 204 differentially expressed ubiquitin related genes (URGs) were identified from The Cancer Genome Atlas (TCGA) cohort, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…An integrated analysis of glycolysis-related genes in clear cell renal cell carcinoma (ccRCC) by Lv et al using TCGA and GEO datasets resulted in the construction of a seven-gene signature that predicted OS in ccRCC ( 17 ). The accuracy and generalizability of a prognostic signature for ccRCC created by Wu et al based on ubiquitin-related genes has been verified in an independent dataset derived from the ArrayExpress database ( 18 ). Verbiest et al found that the ccRCC molecular subtypes (ccrcc1 to 4), established based on unsupervised clustering of whole genome mRNA-expression data ( 19 ), could identify molecularly different patient populations and selected patients for systemic therapies, and they were predictive of sunitinib or pazopanib response in metastatic ccRCC ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 94%
“…An integrated analysis of glycolysis-related genes in clear cell renal cell carcinoma (ccRCC) by Lv et al using TCGA and GEO datasets resulted in the construction of a seven-gene signature that predicted OS in ccRCC ( 17 ). The accuracy and generalizability of a prognostic signature for ccRCC created by Wu et al based on ubiquitin-related genes has been verified in an independent dataset derived from the ArrayExpress database ( 18 ). Verbiest et al found that the ccRCC molecular subtypes (ccrcc1 to 4), established based on unsupervised clustering of whole genome mRNA-expression data ( 19 ), could identify molecularly different patient populations and selected patients for systemic therapies, and they were predictive of sunitinib or pazopanib response in metastatic ccRCC ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 94%
“…A study demonstrated that the overexpression of MG53 in melanoma cells confers enhanced resistance to dacarbazine treatment, thereby highlighting its potential as a valuable strategy for improving chemical resistance ). An analysis of ubiquitinrelated genes in the cancer genome atlas queue revealed an association between MG53 and the prognosis of renal clear cell carcinoma (Wu et al, 2021). MG53 can also impede breast cancer progression by suppressing the activation of the PI3K/Akt/mTOR pathway (Wang et al, 2022).…”
Section: Mg53 and Other Cancersmentioning
confidence: 99%
“…One study analyzed ubiquitin-related genes in The Cancer Genome Atlas cohort and found that MG53 was correlated strongly with the grade, stage, and T stage of clear cell renal cell carcinoma. However, the expression of MG53 in patients with clear cell renal cell carcinoma remains to be confirmed ( 54 ).…”
Section: Beneficial Effects Of Mg53 On Cancer Therapymentioning
confidence: 99%